Countries using data to inform education policies - Kelly, Peggy (Education for All, 2021)
How can data be transformed into policy so that children everywhere, even the most disadvantaged, can realize their right to learn? Read how a project has helped countries like Lao PDR, Georgia and Mongolia to just do that.

Viet Nam MICS-EAGLE factsheet - O'Connell, Tara; Quynh, Nguyen; Lan, Le Anh; Nguyen, Hoang Anh; Fushimi, Akihiro; Mizunoya, Suguru; Mishra, Sakshi; Kelly, Peggy (2022)